Pengaruh Risiko Keamanan, Keuangan dan Sosial terhadap Kepercayaan pada Layanan Mobile Payment Aplikasi Dana - Maytita Zafira Putri; Yudi Sutarso; Faizatul Hiqmah (Journal of Business & Banking, 2021)
This study aims to analyze the effect of security, financial and social risks on trust in mobile fintech services using the Dana application, with moderation of religiosity. The research hypothesis states that security, financial and social risks negatively affect trust, and religiosity moderates the relationship between social risk and trust. The sampling technique used was pur-posive sampling and data was collected through questionnaires. This study involved 125 respondents, namely users of mobile payment application named Dana, from Surabaya and Sidoarjo area. SEM PLS is used as a structural model testing. The main finding of this study shows that security risk has a negative effect on trust, however, financial risk has unconfirmed a negative effect on trust. A different finding of this study is that social risk has a positive effect on trust. In the relationship between social risk and trust, this study suggest that religiosity unconfirmed moderates the relationship.